SUPERAÇÃO DE DORMÊNCIA DE SEMENTES DE ILEX PARAGUARIENSIS - PIRES, Valdirene da Silva; SANTOS, Stephany; OLIVEIRA, Manoel Garcia; SILVA, Gabriel Ojeda; MENDONÇA, Cristiane Gonçalves (ANAIS DO ENIC, 2025)
-